Responsible tourism, destination sustainability and quality of life: a preliminary finding - Ahmad Puad, Mat Som; Muaz, Azinuddin; Aikal Liyani, Mohd Rasdi (IDOSI Publications, 2020)
Apart from the positive economic impact, tourism also gives negative impact to destinations, affecting their environmental and socio-cultural elements of communities living in the areas. Sustainability principles refer to the environmental, economic and socio-cultural aspects of tourism development, therefore, sustainable tourism should utilize the optimal environmental resources that are key elements in tourism development, maintain important ecological processes and also help conserve natural resources and biodiversity. Due to several sustainability challenges, responsible tourism was introduced to enhance current sustainable tourism development. The principles of responsible tourism are developing a win-win situation between minimizing the negative effects and benefiting the host community and contributing positively to the preservation of nature and culture. This paper presents a preliminary finding on the relationship between responsible tourism and quality of life as well as the relationship between destination sustainability and quality of life. The researcher used an online survey as the method of data collection and data was analysed using SPSS. The results showed that responsible tourism and destination sustainability had a significant relationship with quality of life. From the results, it indicates that implementation of sustainable practices are important for a good quality of life among local communities.